Effect of Red Betel Infusion Perineal Care on Healing Time of Perineal Grade I Wounds Postpartum - Shentya Fitriana (International Journal of Science and Society, 2023)
Most women who give birth sustain perineal injuries, which can lead to postpartum infections. Red betel infusion is recognized as one of the simple, inexpensive, and risk-free perineal wound care therapies; it also promotes perineal wound healing and possesses potent antimicrobial properties. This study seeks to determine the effect of perineal care infusion of red betel on postpartum perineal wound healing time at the Duren Sawit District Health Center in East Jakarta in 2022. The study employed the Quasi-Experiment methodology in conjunction with the Nonequivalent Pretest-Posttest Control Group Design research design. A sample of 38 samples was collected using a non-probability sampling technique and an accidental sampling approach. Based on the results of the Mann Whitney test, the p-value was 0.001, indicating that there was a difference in perineal care administration of red betel infusion on the healing time of the postpartum perineal wound between the red betel infusion group and the control group. Other researchers are anticipated to use red betel infusion media by adding variables relating to pain, redness, symptoms of inflammation, and wound healing processes, as well as respondents.